UMPSA residents enliven Khatam al-Quran Ceremony and World #QuranHour - Siti Nurfarmy, Ibrahim (UMPSA, 2024)
GAMBANG, 4 April 2024 – A total of 150 staff of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) graced the Khatam al-Quran and World #QuranHour Ceremony which took place at the UMPSA Mosque of the Gambang Campus recently.